2022
DOI: 10.1039/d1sc05319a
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous sodium four-coordinate aluminosilicate nanoparticles modulate dendritic cell pyroptosis and activate innate and adaptive immunity

Abstract: Na-IVAl-DMSN acts as both antigen carriers and modulators to “hyperactivate” dendritic cells (DCs) via potassium (K+) efflux dependent pyroptosis, eventually leading to enhanced adaptive and innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Proinflammatory cytokines are able to mediate tumor cell death via multiple apoptotic pathways [ 34 36 ]. To determine the tumor-killing activity of Zn 2+ as an artificial proinflammatory cytokine, cell viability assay was carried out on 4T1, 3T3 and L02 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Proinflammatory cytokines are able to mediate tumor cell death via multiple apoptotic pathways [ 34 36 ]. To determine the tumor-killing activity of Zn 2+ as an artificial proinflammatory cytokine, cell viability assay was carried out on 4T1, 3T3 and L02 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on NMs and DCs have focused on their application in nanomedicine, particularly cancer therapy, including research on manipulating immune responses against tumors and novel vaccine formulations. Tang et al demonstrated that sodium-stabilized mesoporous alumino-silicate NMs induce pyroptosis in DCs by releasing a Na + surge in a pH-responsive manner ( Tang et al, 2022 ). This event subsequently triggers pro-inflammatory factor production, thereby amplifying antitumor immune responses.…”
Section: Definition and Classification Of Pyroptosismentioning
confidence: 99%
“…[147] Tang et al reported that sodium-stabilized mesoporous aluminosilicate nanoparticles (Na-IV Al-DMSN) induced pyroptosis in DCs by releasing large amounts of Na + in a pH-responsive manner. [148] The resulting pyroptotic DCs released pro-inflammatory cytokines, such as IL-1𝛽 and IL-18, which activated peripheral DCs and NK cells, enhancing immune responses. [149,150] Furthermore, nanomaterials can also induce pyroptosis by disrupting normal mitochondrial metabolic processes.…”
Section: Pyroptosis Activation Via the Canonical Pathway-enhanced Imm...mentioning
confidence: 99%